2013
DOI: 10.1159/000339432
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of BRCA1 Germ-Line Mutation Status in Patients with Breast Cancer Using Histoprognosis Grade, MS110, Lys27H3, Vimentin, and KI67

Abstract: Family structure, lack of reliable information, cost, and delay are usual concerns when deciding to perform BRCA analyses. Testing breast cancer tissues with four antibodies (MS110, lys27H3, vimentin, and KI67) in addition to grade evaluation enabled us to rapidly select patients for genetic testing identification. We constituted an initial breast cancer tissue microarray, considered as a learning set, comprising 27 BRCA1 and 81 sporadic tumors. A second independent validation set of 28 BRCA1 tumors was matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
2
10
0
Order By: Relevance
“…However, clinically hormone therapy prevents development and suppresses the progression of BRCA1 -deficient, ER-negative breast cancers [ 3 , 4 ]. Inspired by the finding that a fraction of BRCA1 -deficient human and mouse tumor cells harbor EMT features [ 16 19 , 22 24 , 39 , 44 ], and the finding that E2 enhanced the heterogeneity of p18 −/− ;Brca1 MGKO and p16 −/− ; Brca1 MGKO tumors with elevated squamous metaplasia and spindle-shaped cells (typical morphological characteristics of mesenchymal cells), we hypothesized that estrogen promotes EMT and stimulates BRCA1 -deficient, ER-negative tumorigenesis independent of ER. We found by western blot analysis that E2-treated p18 −/− ;Brca1 MGKO tumors expressed a higher level of EMT marker (Vim) and EMT-inducing transcription factors (EMT-TFs) including p-Fra1 and Snail, than placebo-treated tumors.…”
Section: Resultsmentioning
confidence: 99%
“…However, clinically hormone therapy prevents development and suppresses the progression of BRCA1 -deficient, ER-negative breast cancers [ 3 , 4 ]. Inspired by the finding that a fraction of BRCA1 -deficient human and mouse tumor cells harbor EMT features [ 16 19 , 22 24 , 39 , 44 ], and the finding that E2 enhanced the heterogeneity of p18 −/− ;Brca1 MGKO and p16 −/− ; Brca1 MGKO tumors with elevated squamous metaplasia and spindle-shaped cells (typical morphological characteristics of mesenchymal cells), we hypothesized that estrogen promotes EMT and stimulates BRCA1 -deficient, ER-negative tumorigenesis independent of ER. We found by western blot analysis that E2-treated p18 −/− ;Brca1 MGKO tumors expressed a higher level of EMT marker (Vim) and EMT-inducing transcription factors (EMT-TFs) including p-Fra1 and Snail, than placebo-treated tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Möbus, University of Ulm, Ulm, Germany (BrCa-MZ-01) [6]. BRCA1 and BRCA2 gene status was checked for each cell line by full sequencing, as previously described [7]. The cell lines were grown using recommended culture conditions, as previously described [5].…”
Section: Methodsmentioning
confidence: 99%
“…Our data showed that the BRCA1 rs80350973 mutation is only associated with high Ki‐67 index in Chinese patients with TNBC ( P = 0.004). A previous study showed that overexpression of Ki‐67 was associated with BRCA1 mutation and was an indicator of poor prognosis in TNBC . Thus, we sought to determine if the rs80350973 mutation could contribute to shorter DFS.…”
Section: Discussionmentioning
confidence: 99%